Cardiovascular Activities of of the bradykinin system - Jagdish N. Sharma (The Scientific World Journal)
All the components of the kallikrein-kinin system are located in the cardiac muscle andits deficiency may lead to cardiac dysfunction. In recent years, numerous observationsobtained from clinical and experimental models of diabetes, hypertension, cardiacfailure, ischemia, myocardial infarction, and left ventricular hypertrophy have suggestedthat the reduced activity of the local kallikrein-kinin system may be instrumental for theinduction of cardiovascular-related diseases. The cardioprotective property of theangiotensin-converting enzyme inhibitors is primarily mediated via a kinin-releasingpathway, which may cause regression of the left ventricular hypertrophy in hypertensivesituations. The ability of kallikrein gene delivery to produce a wide spectrum of beneficialeffects makes it a promising candidate in treating hypertension and cardiovascular andrenal diseases. In addition, stable kinin agonists may also be available in the future astherapeutic agents for cardiovascular and renal disorders. However, there are alsopossibilities of adverse effects that may be caused by these compounds.